Islamic Literacy in Education: A Comprehensive Analysis of Linguistic and Curriculum Practices - Hasibuan, Kalayo; Amanda Aindilalaty; Andini Putri; Maitri Ramadhani (Journal of Applied Linguistics, 2025)
Islamic institutions that teach English as a foreign language (EFL) face the dual challenge of maintaining religious values while enhancing global communication skills. This study applies the Spiral Andromeda Philosophy a multilevel framework encompassing supra, macro, meso, and micro levels to explore the integration of Islamic literacy into EFL instruction. Employing a qualitative document analysis method, data were collected from curriculum guides, lesson plans, and educational texts used in Islamic learning settings. Thematic findings reveal that incorporating Islamic elements such as Quranic passages, historical narratives, and ethical discussions not only supports language development but also strengthens moral awareness. Key strategies include curriculum integration, contextualized learning, interactive pedagogical practices, and assessments aligned with Islamic values. The results show that aligning EFL teaching with Islamic principles enhances student engagement, ethical communication, and identity formation, offering a holistic educational experience within Islamic institutions. Keywords : Spiral Andromeda, Islamic literacy, language instruction, curriculum integration, moral education